Study on the lifetime of photocatalyst by photocatalytic membrane reactors (PMR) - Yan, Xiaoju (Water science and technology : a journal of the International Association on Water Pollution Research, 2020)
The continuously photocatalytic degradation of methyl orange (MO) was carried out using a photocatalytic membrane reactor (PMR). The lifetime, cause of deactivation, and regeneration of Degussa P25 titanium dioxide (TiO2) were investigated. The photocatalyst was deactivated when the concentration of MO in the effluent of the PMR was stable. To characterize the lifetime of the photocatalyst, we applied g MO/g TiO2. The lifetime of the photocatalyst during the photocatalytic degradation of 10 mg/L MO was 3.71 times that of 5 mg/L MO. Changing the hydraulic retention time of the PMR from 0.75 to 3 h prolonged the lifetime of the photocatalyst. Deactivation of the photocatalyst was not due to pore blocking by the reactant (MO) or intermediate products. The surface adsorption of MO and the reaction intermediates deactivated the catalyst. The spent catalysts were regenerated after washing with methanol and hydrogen peroxide (H2O2) and then treated with heat. H2O2 treatment generated the highest regeneration rate, because H2O2 is a strong oxidizing agent that oxidized the deposited species on the surface of the photocatalyst